(untitled) (Communications in Computational Physics, 2014)
Numerical error caused by "ghost forces" in a quasicontinuum method is studied in the context of dynamic problems. The error in the discrete W1,∞ norm is analyzed for the time scale O(ε) and the time scale O(1) with ε being the lattice spacing.